Integrating global Englishes activities in a regular English classroom - Sirinmas Sangpetch; Punwalai Kewara; Denchai Prabjandee (Universitas Ahmad Dahlan, 2023)
The purposes of this qualitative study were to integrate Global Englishes (GE) activities into a regular classroom and to explore how GE activities influenced: a) students’ attitude toward Global Englishes, b) respect for the variety of English, and c) the use of English in daily life. The participants were 31 Grade 9 Thai students. Designed GE lesson plans, adapted from the Global Englishes Language Teaching (GELT) framework, video recordings, were used to explore the classroom environment and to observe each activity. The researcher’s reflections were used to see the participants’ attitudes and reactions toward GE activity. The findings revealed that integrating GE-oriented activities in a regular English classroom is possible. The participants respect and tend to have positive attitudes toward the varieties of Englishes. The results, however, revealed that most participants hardly ever use English to communicate in daily life outside of what they learn in the classroom. Furthermore, this study offers examples of GE activities and materials that teachers can use as a model for designing and implementing GE activities that are appropriate for various classroom settings.